IMPLEMENTASI FATWA MUI NOMOR: 108/DSN-MUI/X/2016 TENTANG PEDOMAN PENYELENGGARAAN PARIWISATA BERDASARKAN PRINSIP SYARIAH TERHADAP WISATA SYARIAH TELAGA BIRU PARK DI KABUPATEN WAJO - Wana Ikhwana; Hasanna Lawang; Syarifa Raehana (STKIP Subang, 2026)
This study uses a qualitative approach with the following approaches: sociological, normative theological, and juridical. The data sources for this study are interviews with the managers and visitors of Telaga Biru Park Sharia Tourism, and the people of Lempong Village. Furthermore, the data collection methods used are observation, interviews, and documentation. The findings show that the management mechanism is carried out by the Islamic boarding school administrators and the surrounding community, and that the sharia tourism services at TelagaBiru Park are running well with adequate facilities. However, the sharia tourism practices at Telaga Biru Park have not fully implemented DSN MUI Fatwa No. 108/DSN-MUI/X/2016 regarding guidelines for organizing tourism based on sharia principles. This is evident from the lack of facilities to separate the men's and women's pools, which are not covered, so that the curves of the body caused by the clothing sticking to the body when swimming can be seen by the opposite sex. There are also male visitors who like to swim in the women's pool when the pool supervisor is not paying attention, and vice versa.